EFEKTIVITAS PEMBERIAN METODE BIRTH BALL TERHADAP INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF DI BPM ROKAN HULU - Rahmi Fitria; Romy Wahyuny (Fakultas Ilmu Kesehatan, 2021)
Childbirth is a natural process. Physiologically, in labor, there will be contractions that cause cervical thinning and opening. Labor pain is a physiological part of the labor process with a different pain intensity for each individual. Many methods are used to reduce pain during childbirth, one of which is by using the birth ball method. Birth ball is a method of using a rubber ball filled with air which is used to reduce back pain during pregnancy and childbirth. This study aims to determine the effectiveness of the birth ball method, which is one of the non-pharmacological methods in reducing the pain of labor during the first stage of the active phase in BPM Rokan Hulu. To compare the intensity of labor pain before andafter the birth ball method was given. The sample of this research was 31 women who gave birth, obtained by simple random sampling technique. Bivariate analysis was performed using the t-dependent test. The results showed that the average labor pain amongrespondents before being given birth ball exercises was 0.259 times higher than that after exercise with a p-value of 0.00. There is a significant effect on the intensity of labor pain during the active phase of the first stage after being given a birth ball training with before being given a birth ball exercise. The intensity of the first stage labor pain in the respondents decreased after being given birth ball exercises.